Biochar as Reinforcement for Composite Materials in the Automotive Industry - Fauzi Ibrahim; Ambar Pambudi; Randi Anggit Wibisono (Fakultas Teknik Universitas Malahayati, 2026)
Biochar, also referred to as biocarbon when positioned as an engineering filler, is a carbon-rich solid obtained by thermochemical conversion of renewable biomass and organic waste under oxygen-limited conditions. Its low density, tunable surface chemistry, porous morphology, thermal stability and potential carbon-storage value make it a promising reinforcement for polymer composites in the automotive industry. This article reviews the use of biochar as a reinforcing phase in polypropylene, polylactic acid, polyamide, epoxy and rubber composite systems from an engineering design perspective. The review focuses on the interaction between feedstock, pyrolysis temperature, ash and carbon content, particle-size distribution, interfacial bonding, melt-processing behavior and automotive qualification requirements. Literature evidence shows that biochar can increase tensile and flexural stiffness, improve heat-deflection resistance, reduce smoke and heat release, and provide a mass advantage compared with mineral fillers. However, strength and impact performance are strongly non-monotonic and can degrade when agglomeration, high viscosity, weak wetting or excessive ash content dominate the microstructure. A proposed Automotive Biochar Composite Readiness Index is introduced to compare matrix-specific readiness for interior trim, instrument-panel carriers, under-hood covers, battery-enclosure inserts, rubber compounds and additive-manufactured fixtures. The analysis indicates that near-term implementation is strongest for semi-structural and non-structural parts, whereas crash-critical structures require hybridization, robust CAE material cards and full ageing, fire, fogging, odor and life-cycle assessment. The paper concludes with a qualification roadmap and design rules for translating laboratory biochar composites into automotive-grade materials.